Lactulose and Melibiose Attenuate MPTP-Induced Parkinson’s Disease in Mice by Inhibition of Oxidative Stress, Reduction of Neuroinflammation and Up-Regulation of Autophagy - Lin, Chih-Hsin; Wei, Pei-Cih; Chen, Chiung-Mei; Huang, Yu-Ting; Lin, Jia-Lan; Lo, Yen-Shi; Lin, Jia-Li; Lin, Chung-Yin; Wu, Yih-Ru; Chang, Kuo-Hsuan; Lee-Chen, Guey-Jen (Frontiers in Aging Neuroscience, 2020)
Parkinson’s disease (PD) is a common neurodegenerative disease characterized by progressive loss of dopaminergic (DAergic) neurons in ventral brain. A disaccharide trehalose has demonstrated the potential to mitigate the DAergic loss in disease models for PD. However, trehalose is rapidly hydrolyzed into glucose by trehalase in the intestine, limiting its potential for clinical practice. Here we investigated the neuroprotective potentials of two trehalase-indigestible analogs, lactulose and melibiose, in sub-chronic 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced mouse model of PD. Treatment with MPTP generated significant motor deficits, inhibited dopamine levels and down-regulated dopamine transporter (DAT) in striatum. Expression levels of genes involved in anti-oxidative stress pathways, including superoxide dismutase 2 (SOD2), nuclear factor erythroid 2-related factor 2 (NRF2) and NAD(P)H dehydrogenase (NQO1) were also down-regulated, while expressions of oxidative stress marker 4-hydroxynonenal (4-HNE), microglial activation marker ionized calcium-binding adapter molecule 1 (IBA1) and astrocyte activation marker glial fibrillary acidic protein (GFAP) in ventral midbrain were up-regulated following MPTP treatment. MPTP also reduced the activity of autophagy, evaluated by autophagosomal marker microtubule-associated protein 1 light chain 3 (LC3)-II. Lactulose and melibiose significantly rescued motor deficits, increased dopamine in striatum, reduced levels of 4-HNE, IBA1 and GFAP, up-regulated SOD2, NRF2 and NQO1 levels, as well as LC3-II/LC3-I ratio in ventral midbrain with MPTP treatment. Our findings indicate the potential of lactulose and melibiose to protect DAergic neurons in PD.